THE IMPACT OF LANGUAGE CHANGES CAUSED BY TECHNOLOGY AND SOCIAL MEDIA - Natsir, Nurasia; Aliah, Nuraziza; Zulkhaeriyah, Zulkhaeriyah; Amiruddin, Amiruddin; Esmianti, Farida (Universitas Islam Sumatera Utara (UISU), 2023)
This research discusses language change as a result of the influence of social media. In an increasingly advanced digital era, social media has become one of the primary communication tools for individuals worldwide. This study utilizes descriptive and comparative analysis methods to explore the influence of social media on language change. Firstly, the research identifies grammar, syntax, and vocabulary changes due to social media usage. Then, the study compares the language used in traditional communication with that used in social media communication. The findings of this research indicate significant language changes due to the use of social media. There is an increase in the use of abbreviations, emoticons, and distinctive terms specific to social media that affect the way humans communicate in a digital context. Additionally, casual writing styles, non-formal language use, and the adaptation of foreign words have become characteristics of social media communication. These language changes can have both positive and negative impacts. On the positive side, social media has enabled faster and more efficient communication between individuals across the globe. Using a more casual and non-formal language can also strengthen social bonds among social media users. However, on the other hand, these language changes can also pose challenges to understanding and communication between different generations or in formal contexts.